Sequential use of oral and vaginal misoprostol versus oral or vaginal misoprostol alone for induction of labor and the caesarean delivery risk: a retrospective study - George, Anu Anna; Francis, Amala Rita; Zachariah, Pavithra Sosa; Isac, Mini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Induction of labor is now a common practice and every institute faces the task of developing a safe and cost-effective protocol. We aimed to study the effects of sequential use of oral and vaginal misoprostol when compared to oral or vaginal misoprostol alone. Our primary objective was to determine the caesarean delivery rates and secondarily the maternal and neonatal complications between the different induction regimes. Methods: A single-center retrospective observational study was conducted, with patient records divided into three groups based on their methods of induction: those who were administered vaginal misoprostol only, those who had oral misoprostol only, and those who had oral misoprostol followed by vaginal misoprostol. We extracted all the necessary data from the records and analyzed it using SPSS. Results: 768 records with comparable demographic characteristics were reviewed. The majority of women were induced at 39 completed weeks. There was no significant difference in the proportion of caesarean deliveries when comparing the three groups but the number of caesarean sections was lower among women who had been administered vaginal misoprostol alone. Among the patients included in the study, the women who developed postpartum hemorrhage received a higher mean dose of misoprostol (130±70 mcg) compared to those who did not (104±57 mcg). Conclusions: Sequentially administering misoprostol may not decrease the caesarean section rate compared to using only one route of administration. However, it is important to monitor the amount of misoprostol given to each patient to prevent the incidence of PPH.